Determinansi Kinerja Keuangan Pemerintah Daerah - Sri Winarsih Ramadana; Mariana Mariana; Rahmaniar Rahmaniar; Saiful Bahgia (Politeknik Ganesha Medan, 2023)
This study aimed to determine the effect of capital expenditure and accrual directors on financial performance in Aceh local government. The research method used is a quantitative approach using secondary data. The data analysis method used in this research is multiple linear regression. The population in this study were all districts/cities in Aceh Province, totalling 23 City Districts, with the observation year taken being 2017-2019. From 23 samples with three years of observation, 69 observations were obtained. The results showed that capital expenditure affects the financial performance of local governments. However indicates that local governments make capital expenditures appropriately and effectively, so this can improve the financial performance of local governments. Accrual directors affect the financial performance of local governments. However, by using an accrual accounting system, directors can better evaluate the financial performance of local governments.